The Influence Of Digital Leadership On Employee Performance Is Mediated By Work Engagement Of Academic Employees - Pardede, Surya Darma; Yusnadi, Yusnadi; Ahmad, Selamat Trinono; Dalimunthe, Muhammad Bukhori; Baharuddin, Baharuddin (Jurnal Mamangan, 2023)
In the digital era, leaders are required to be able to integrate technology in the management and operations of educational institutions. According to Khan & khan (2021) digital leadership not only focuses on the use of technology but also how technology can improve the performance of employees and the organisation as a whole based on bibliometric analysis using the VOSviewer application shows that 315 relevant articles were obtained which accounted for 60% of the total articles found that network visualisation that has discussed many research linkages of digital leadership with technology while leadership ledearship with wrok engagement and performance is still small. The purpose of this study is to explore the effect of digital leadership on academic staff performance at HKBP Nommesen University and to investigate how work engagement can mediate the relationship. The research question posed was: ‘is it suspected that digital leadership has a significant effect on work engagement directly’, “is it suspected that digital leadership has a significant effect on employee performance directly”, “is it suspected that work engagement has a significant effect on employee performance through work engagement?”. Based on the results of the discussion, it can be concluded that, based on calculations using SmartPLS 4.0 software, there is a significant effect of digital leadership on improving employee performance with path coefficient (0.307) and p-value (0.002 <0.05) with a structural level of influence at a low level (F square = 0.084). There is a significant effect of digital leadership on increasing Wrok Engagement with path coefficient (0.507) and p-value (0.000 < 0.05) with structural influence at moderate level. there is no significant effect of Wrok engagement on improving employee performance with path coefficient (0.149) and p-value (0.115 > 0.05). because there is no significant effect of digital leadership on performance through Wrok engagement as an intervening variable with path coefficient (0.076) and p-value (0.120 > 0.05)